”Rent Seeking Behaviour” dalam Relasi birokrasi dan Dunia Bisnis - Syamsul Ma'arif (NATAPRAJA, 2011)
Private sector is one of the important element in the economic system driven by mar ket mechanism. It means that development process needs the entrepreneur group which is characterized as competitive and independent. However in Indonesia, this faction never grew yet since Indonesia took independence. What happened in Indonesia is the rise of group named “ client entrepreneur “ ( client businessmen) which  their existence is highly dependent on the “patronage” and protection given by the state. While economic globaliza tion which recently wide spreads over the world demands governments to reduce their in volvement in many economic activity in order to increase the role of private sector. This last phenomenon happened since too large involvement of government bureaucracies have resulted failure and un-efficiency. That’s why numerous countries, including to Indonesia, conducted economic reforms to open the greater room to market mechanism.   Keywords : businessmen, bureaucracy, economics